Kvantno računanje - Belič, Igor (Vakuumist, 1996)
Where will new directions in computer technologies go is the main question of the original paper writtenby Tom Thompson and published by Byte. There is a particularly interesting section describing the potentials of quantum computing that requires the vacuum system in order to operate. If the quantum computing story ever comes true will also be the moment of great vacuum technology expansion.
Keywords: computer science; računalništvo; kvantni procesorji; vakuumska tehnika